Endoscopic and Histological Mucosal Healing in Ulcerative Colitis in the First Year of Diagnosis: Results from a Population-based Inception Cohort from Six Countries in Asia. (26th July 2017) - Leung, Choy May; Tang, Whitney; Kyaw, Moe; Niamul, Gani; Aniwan, Satimai; Limsrivilai, Julajak; Wang, Yu-Fang; Ouyang, Qin; Simadibrata, Marcellus; Abdullah, Murdani; Ong, David E; Yu, Hon Ho; et al.
Abstract: Background and Aims: Mucosal healing is associated with improved long-term clinical outcomes in patients with ulcerative colitis. This population-based study assessed endoscopic and histological mucosal healing within the first year of diagnosis. Methods: Consecutive patients diagnosed with ulcerative colitis from six countries in Asia were prospectively enrolled. Clinical demographics, blood markers and inflammatory activity were assessed at baseline. Mayo score and Nancy index were used to assess endoscopic and histological activities, respectively. Clinical, endoscopic and histological evaluations were repeated at 1 year. Logistic regression was performed to identify predictors of mucosal healing. Results: Of 433 ulcerative colitis patients, 202 [46.7%] underwent colonoscopy at 1 year. In total, 68 [38.2%] achieved endoscopic mucosal healing and 35 [23.1%] achieved histological mucosal healing. On multivariate analysis, an elevated erythrocyte sedimentation rate [ESR] at diagnosis (odds ratio [OR], 0.332; 95% confidence interval (CI), 0.133–0.830; p = 0.018) was a significant negative predictor of endoscopic mucosal healing at 1 year, while histological features of ulceration [OR, 0.156; 95% CI, 0.028–0.862; p = 0.033] and being an ex-smoker [OR, 0.067; 95% CI, 0.005–0.965; p = 0.047] were significant negative predictors of histological healing at 1 year. Both endoscopic and histological mucosal healing were associated with less steroid use [ p < 0.001 and p = 0.001, respectively] and hospitalization [ p = 0.002 and p = 0.01, respectively]. Conclusions: Mucosal healing was achieved in fewer than half of patients with ulcerative colitis in the first year of diagnosis. An elevated ESR predicted less likelihood of endoscopic mucosal healing, while histological features of ulceration and being an ex-smoker at diagnosis predicted less likelihood of histological healing.